Management of Training Process of Team Sports Athletes During the Competition Period on the Basis of Programming (Football-Based) - Natalia Shchepotina; Viktor Kostiukevych; Inna Asauliuk; Vadym Stasiuk; Tetiana Vozniuk; Svitlana Dmytrenko; Vadym Adamchuk (Physical Education Theory and Methodology, 2021)
The purpose of the study was to experimentally substantiate the effectiveness of organization of structural arrangements of the training process in skilled football players within the limits of the competition period on the basis of programming.